MEMBERDAYAKAN NASABAH MENGHADAPI CARUT MARUT PROGRAM RESTRUKTURISASI JIWASRAYA MELALUI INSTRUMEN HUKUM PERLINDUNGAN KONSUMEN - Mikhaill Nuryansah, (2022)
The increasing development of insurance creates many variations of insurance service products offered to the public, such as life insurance, health insurance, business insurance, vehicle insurance, and others. Even today, many insurance companies offer insurance products including an investment. While investing, The Policyholder must apply the principle of prudence. However, there are companies that do not implement this principle in practice. This study discusses the legal protection of consumers in the dispute resolution of insurance company and the optimization of it. The research uses the Act Approach method which involves legislation and regulations, also uses a case approach for reference. The conclusion is there still problem along the process with the negative confirmation and, The Policyholder and the guarantee companies being charge of the company's obligations and restructuring which not in line with disclosure and fairness. Suggestions that can be offered by proposing to the President to revoke the transfer of obligations of PT Asuransi Jiwasraya, establish more comprehensive legal rules related to insurance as well as supervision of the Insurance Industry sector, return and provide compensation to Jiwasraya customers and a special team in fact-finding problems.